Reassessing Egalitarianism - Moss, J. author. aut Link
VII, 180 p.
Keywords: Through an analysis of the different dimensions of equality, this book provides a critical introduction to recent philosophical work on egalitarianism, discussing the central questions associated with each of the major debates about egalitarian justice.